The Relationship Between Self-Regulation Skills for Learning and Academic Endurance Among Students of the Babylon Technical Institute - Salih, Awatif Hameed; Mandeel, Farah Majeed (Journal of Innovation in Education and Social Research, 2026)
This research aims to study the relationship between self-regulation skills for learning and students' academic endurance. The research highlights how self-regulation skills influence students' learning and academic endurance by enhancing democratic practices. Promoting innovation and increasing social and psychological stability. The results showed that students with self-regulation skills demonstrated a high capacity for learning and resilience, and also showed improvement in their academic performance. One of the most notable findings was that students who followed policies that encouraged the relationship between different skills showed a 35% improvement in academic performance, learning ability, and resilience. The study also showed that self-learning skills affect its ability to enhance and improve learning and academic endurance. Key recommendations include embracing lifelong learning, utilizing diverse resources, setting goals, encouraging continuous learning, practicing self-discipline, promoting positive thinking, engaging in ongoing training, managing personal emotions effectively, fostering strong professional relationships, and collaborating with others. The research demonstrates the importance of the relationship between self-regulation skills and academic endurance among students at the Babylon Technical Institute.